Evaluating the relationship between change in performance on training tasks and on untrained outcomes - Zelinski, Elizabeth M.; Peters, Kelly D.; Hindin, Shoshana; Petway, Kevin T.; Kennison, Robert F. (Frontiers in Human Neuroscience, 2014)
Training interventions for older adults are designed to remediate performance on trained tasks and to generalize, or transfer, to untrained tasks. Evidence for transfer is typically based on the trained group showing greater improvement than controls on untrained tasks, or on a correlation between gains in training and in transfer tasks. However, this ignores potential correlational relationships between trained and untrained tasks that exist before training. By accounting for crossed (trained and untrained) and lagged (pre-training and post-training) and cross-lagged relationships between trained and untrained scores in structural equation models, the training-transfer gain relationship can be independently estimated. Transfer is confirmed if only the trained but not control participants' gain correlation is significant. Modeling data from the Improvement in Memory with Plasticity-based Adaptive Cognitive Training (IMPACT) study (Smith et al., 2009), transfer from speeded auditory discrimination and syllable span to list and text memory and to working memory was demonstrated in 487 adults aged 65–93. Evaluation of age, sex, and education on pretest scores and on change did not alter this. The overlap of the training with transfer measures was also investigated to evaluate the hypothesis that performance gains in a non-verbal speeded auditory discrimination task may be associated with gains on fewer tasks than gains in a verbal working memory task. Gains in speeded processing were associated with gains on one list memory measure. Syllable span gains were associated with improvement in difficult list recall, story recall, and working memory factor scores. Findings confirmed that more overlap with task demands was associated with gains to more of the tasks assessed, suggesting that transfer effects are related to task overlap in multimodal training.